2005
DOI: 10.1097/00005082-200505000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Training Effect Associated With Polestriding Exercise in Patients With Peripheral Arterial Disease

Abstract: Because individuals with claudication pain secondary to peripheral arterial disease (PAD) are limited in both walking speed and duration, the benefits of walking exercise may be insufficient to yield a cardiovascular training effect. The objectives of this analysis were to determine whether polestriding exercise training, performed by persons with PAD, would improve exercise endurance, elicit a cardiovascular training benefit, and improve quality of life (QoL). Persons (n = 49) whose claudication pain limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 23 publications
1
77
0
2
Order By: Relevance
“…The findings of significant associations between changes in submaximal exercise and peak exercise fitness parameters and improvement in walking distances with both forms of exercise training are consistent with those of previously published reports. 5,10,12,13,30 These findings suggest that improved central cardiorespiratory fitness with both arm-ergometer and lower body-exercise training defers the onset of claudication pain during walking in PAD patients and contributes significantly to improved MWD. The observed improvement of walking distances after exercise training was previously postulated to be related to local skeletal muscle metabolic changes, improved vascular endothelial reactivity, blood rheologic changes, and local and central blood flow adaptations.…”
Section: Discussionmentioning
confidence: 91%
“…The findings of significant associations between changes in submaximal exercise and peak exercise fitness parameters and improvement in walking distances with both forms of exercise training are consistent with those of previously published reports. 5,10,12,13,30 These findings suggest that improved central cardiorespiratory fitness with both arm-ergometer and lower body-exercise training defers the onset of claudication pain during walking in PAD patients and contributes significantly to improved MWD. The observed improvement of walking distances after exercise training was previously postulated to be related to local skeletal muscle metabolic changes, improved vascular endothelial reactivity, blood rheologic changes, and local and central blood flow adaptations.…”
Section: Discussionmentioning
confidence: 91%
“…In this way, NW could represent an attractive activity particularly for overweight or obese individuals who need to increase their intensity of walking in order to enhance their energy expenditure, but who also present walking speed limitations. Positive effects of the NW exercise program were reported not only in patients with cardiovascular diseases (Collins et al 2005), rheumatic syndrome (Strombeck et al 2007), Parkinson's disease (Baatile et al 2000;van Eijkeren et al 2008), but also in depressed patients (Suija et al 2009) and in breast cancer survivors (Sprod et al 2005). To our knowledge, effects of NW in obese middleaged individuals have never been investigated.…”
Section: Introductionmentioning
confidence: 96%
“…Of these, 24 journal articles met defined selection criteria. Authors confirmed that two publications reported on the same group of patients [7,8]. Therefore the final number of studies was 23, of which five were randomised controlled trials [7][8][9][10][11][12] (see Table 1).…”
Section: Resultsmentioning
confidence: 79%